Influence of the storage conditions (Frozen vs. Dried) in health-related lipid indexes and antioxidants of bee pollen - Estevinho, Leticia M. (2018)
Following harvest, bee pollen must be submitted to processing in order to maintain properties for consumers’ health insurance. In this study, the changes on the lipid profile, contents of vitamin C, β-carotene and lycopene of bee pollen samples submitted to two conservation methods (freezing and drying) are evaluated. Eleven fatty acids, eight saturated, one monounsaturated, and two polyunsaturated are quantified. The PUFA/SFA ratio ranges from 1.18 to 3.95 g 100−1 g−1 and is significantly higher in the frozen extracts. On the other hand, the ratio n6:n3 (ranging between 0.36 and 0.86 g 100−1 g−1) did not differ among processing methodologies, for most of the cases. The atherogenicity (AI) and thrombogenecity (TI) indexes are similar among preservation processes and coherent with the found on other health-promoting foods. The contents of vitamin C, β-carotene and lycopene are, for all samples, significantly superior in the frozen bee pollen. Practical Applications: In the recent years the interest in natural products has mushroomed. Indeed, in addition to the good nutritional composition bee pollen possesses important bioactive compounds and promising health promoting activities that remain unstudied. In this study, it is evaluated the influence of the geographical origin and two storage methods (drying and freezing) in the fatty-acid profile, lycopene, vitamin C and β-carotene contents and on two lipid indexes of bee pollen. Results suggest that bee pollen may act as a complement for the prevention of atherosclerosis and thrombogenesis. Regarding storage it wi inferred that freezing allows preserving the bioactive compounds in a greater extent and, therefore, must be the preferred method. Further studies may be performed in order to take advantage of this natural products’ potential. From the nutritional point of view, it is better to consume bee pollen frozen in comparison to that of dried.